2000
DOI: 10.1345/aph.19257
|View full text |Cite
|
Sign up to set email alerts
|

Hypertensive Crisis and Myocardial Infarction following Massive Clonidine Overdose

Abstract: Clonidine, although a safe medication with usual dosages, must be used with caution when given in injectable form. An overdose of this alpha-adrenoreceptor agonist can produce significant vasospasm and hypertensive emergency. Drugs used to treat overdose, such as naloxone, can potentiate clonidine's adverse effects, leading to further morbidity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
25
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 17 publications
4
25
0
Order By: Relevance
“…Another clinical study in healthy volunteers reported an 80% increase in systemic vascular resistance following supratherapeutic dexmedetomidine doses (13). These observations are in line with clinical reports on severe arterial hypertension following inadvertent overdoses of a,-agonists ( 14,15). In addition, a^-agonists can interfere with the baroreceptor reflex (changes in heart rate in response to changes in arterial pressure) through central mechanisms.…”
supporting
confidence: 74%
“…Another clinical study in healthy volunteers reported an 80% increase in systemic vascular resistance following supratherapeutic dexmedetomidine doses (13). These observations are in line with clinical reports on severe arterial hypertension following inadvertent overdoses of a,-agonists ( 14,15). In addition, a^-agonists can interfere with the baroreceptor reflex (changes in heart rate in response to changes in arterial pressure) through central mechanisms.…”
supporting
confidence: 74%
“…2 Reported clinical effects from overdose have included hypertension, hypotension, hypothermia, bradycardia, tachycardia, coma, respiratory depression, apnea, generalized hypotonia, hyporeflexia, and miosis. [1][2][3][4][5][6][7][8] Death after overdose is rare, with only a single death reported in one study of more than 10,000 overdoses. 1 The majority of publications on clonidine overdose are anecdotal reports.…”
mentioning
confidence: 99%
“…1 The majority of publications on clonidine overdose are anecdotal reports. [2][3][4][5][6][7][8] Most published studies are retrospective and provide no data on dosage response, toxicodynamic response in overdose, or other critical areas that might help guide the clinician. 1,9 Review of the published case reports shows that prominent onset of adverse clinical effects in the severe cases was rapid, usually in <1 hour.…”
mentioning
confidence: 99%
“…[93][94][95] This elevation in blood pressure, thought to be due to peripheral a 1 -and a 2 -AR agonism, is usually transient, asymptomatic, and does not require treatment. The degree of hypertension is correlated with the significance of the exposure, and higher serum concentrations better correlate with development of hypertension.…”
Section: Clinical Manifestationsmentioning
confidence: 99%
“…96,97 Thus although most cases of elevated blood pressures seen are asymptomatic, massive overdoses with resultant severe-range blood pressures can lead to endorgan manifestations including myocardial infarction, subarachnoid hemorrhage, altered mental status, and seizures. 94,98,99 With respect to heart rate, sinus bradycardia is the most common bradydysrhthymia. 100,101 Tachycardia should not be expected and suggests a coingestion or an alternate diagnosis.…”
Section: Clinical Manifestationsmentioning
confidence: 99%